2019
DOI: 10.1007/s00268-019-04962-8
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Minimally Invasive Hartmann Takedown: A Meta‐analysis of the Literature

Abstract: Although end colostomy closure following Hartmann's procedure is a major surgery that is traditionally performed by conventional celiotomy, over the last decade there has been a growing interest toward the application of different minimally invasive techniques. We aimed at evaluating the relative outcomes of conventional surgery versus minimally invasive surgery by meta-analyzing the available data from the medical literature. The PubMed/ MEDLINE, Cochrane Library and EMBASE electronic databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
(150 reference statements)
5
29
1
1
Order By: Relevance
“…Conversion rates vary greatly in the literature, which may be related to technique, surgical experience or, more likely, patient selection. A recent meta‐analysis demonstrated conversion rates ranging from 0% to 50%, representing substantial heterogeneity in practice and study populations [9]. The significant reduction in SSI observed in the LHR group aligns with prior published series; however, reduction in EBL, overall morbidity and major morbidity were not observed.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Conversion rates vary greatly in the literature, which may be related to technique, surgical experience or, more likely, patient selection. A recent meta‐analysis demonstrated conversion rates ranging from 0% to 50%, representing substantial heterogeneity in practice and study populations [9]. The significant reduction in SSI observed in the LHR group aligns with prior published series; however, reduction in EBL, overall morbidity and major morbidity were not observed.…”
Section: Discussionsupporting
confidence: 70%
“…Successful HR comes with a substantial risk of morbidity, with a 30‐day morbidity rate of over 50%. HR has a high risk of morbidity, with published morbidity rates consistently in the range of 30%–50% [3,4,8,9]. The rate of DLI creation in our series of 21% was higher than in some previously published reports, and may reflect differences in surgical practice or the complexity of surgical cases treated at a tertiary referral centre.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, laparoscopic reversal is beneficial for patients in terms of improved length of stay and 30-day morbidity. Many previous studies showed that the laparoscopic approach to HR should be considered when technically feasible and this approach was associated with fewer complications than open surgery [6,9]. Many different laparoscopic techniques have been described in the literature, but the ideal laparoscopic fashion and the relative advantages of each procedure are still debated.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of anastomotic leakage ranged from 4% to 16%, the mortality rate was up to 10%, and 46.5% of patients had postreversal complications [2][3][4]. In 1993, Lucchetta and De Manzini [5] and Anderson et al [6] published the first report of a laparoscopic colostomy closure for previous HP. Some recent reviews showed that laparoscopic Hartmann reversal (LHR) brings several advantages over OHR, including fast postoperative recovery, less postoperative pain, earlier restoration of bowel function, and reduced morbidity [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, colostomy reversal has been a topic of discussion aimed at reducing morbidity and mortality rates [5,6]. While conventional approaches of Hartmann's reversal [HR] such as open surgery (OS) and conventional laparoscopic (CL) surgery have been preferred, laparoscopic approaches have become increasingly favored by many for its reduced postoperative morbidity, wound infection, length of stay, and ileus formation.…”
Section: Introductionmentioning
confidence: 99%